2018
DOI: 10.20431/2349-0349.0611003
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Environmental Commitment on Financial Performance through Green Innovation

Abstract: The main objective of this research is to demonstrate empirically the effect of environmental commitment on financial performance through green innovation in the manufacturing companies listed in Indonesia Stock Exchange (IDX). This research was conducted by examining the effect of environmental commitment that refer to ISO 14001 as a independent variable on financial performance of the company that using return on equity (ROE) as a dependent variable through green process innovation and green product innovati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
3
0
3
Order By: Relevance
“…In addition, another study was conducted by Tasneem, Muhammad and Basit (2016) indicated that environmental reporting/checks has a positive and significant effect on the performances of the manufacturing firms in the USA. Likewise, Suryani and Dianawati (2018) examined the effect of environmental commitment on the financial performance of manufacturing companies listed in the Indonesia Stock Exchange (IDX). This study shows that environmental commitment has a positive and significant effect on financial performance.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…In addition, another study was conducted by Tasneem, Muhammad and Basit (2016) indicated that environmental reporting/checks has a positive and significant effect on the performances of the manufacturing firms in the USA. Likewise, Suryani and Dianawati (2018) examined the effect of environmental commitment on the financial performance of manufacturing companies listed in the Indonesia Stock Exchange (IDX). This study shows that environmental commitment has a positive and significant effect on financial performance.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Penelitian lainnya yang dilakukan oleh Mariyamah & Handayani (2019) terkait green innovation dan environmental management accounting menyatakan bahwa keberlangsungan perusahaan ditentukan oleh proses bisnis yang telah memenuhi aturan atau tidak melanggar batasan yang telah ditentukan oleh masyarakat. Dengan melaksanakan kewajiban perusahaan terhadap lingkungan dan inovasi hijau maka perusahaan akan semakin mudah dalam mendapatkan legitimasi dari masyarakat (Suryani & Dianawati, 2018). Sehingga menurut Ammer dkk.…”
Section: Teori Legitimacyunclassified
“…Hal ini menjadi kunci perusahaan dalam memuwujkan pembangunan hijau (C. Wang & Li, 2020). Green innovation mendukung industri yang berbasis ramah lingkungan serta mengurangi kerusakan lingkungan dari kegiatan produksi yang dilakukan dengan menciptakan inovasi berbasis ramah lingkungan (Suryani & Dianawati, 2018). Dengan banyaknya perusahaan manufaktur yang mulai bermunculan menimbulkan tekanan dari investor untuk bersaing secara kompetitif antar perusahaan.…”
unclassified
“…The study measured the performance using both financial and non-financial indicators. Combining these two measures helps managers gain a broader perspective on measuring and comparing performance hence the extent of effectiveness and efficiency in utilization of resources, competitiveness, and readiness to face the growing external pressures, including globalization (Suryani & Dianawati, 2018).…”
Section: Background Of the Studymentioning
confidence: 99%
“…Likewise, Suryani and Dianawati (2018) examined the effect of environmental commitment on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX). This study shows that environmental commitment has a positive and significant effect on financial performance.…”
Section: Empirical Reviewmentioning
confidence: 99%